River of smoke - Amitav Ghosh (London John Murray, 2011)
"The Ibis, loaded to its gunwales with a cargo of indentured servants, is in the grip of a cyclone in the Bay of Bengal; among the dozens flailing for survival are Neel, the pampered raja who has been convicted of embezzlement; Paulette, the French orphan masquerading as a deck hand; and Deeti, the widowed poppy grower fleeing her homeland with her love, Kalua. The storm also threatens the clipper ship Anahita, Read more...
Keywords: Schooners -- Fiction. Voyages and travels -- Fiction. Sailors -- Fiction